The Low Opportunity Costs of the Amazon Soy Moratorium - Rausch, Lisa L.; Gibbs, Holly K. (Frontiers in Forests and Global Change, 2021)
Brazil’s Amazon Soy Moratorium (ASM) contributed to overall reductions in Amazon deforestation since its implementation in 2006. Under the ASM, the Amazon soy sector maintains access to the growing share of the market that operates under zero-deforestation commitments. The ASM has been criticized as unfair to law-abiding producers. Only 1% of the approximately 14,000 soy farms in the Amazon Biome have soy-suitable, forested areas that could be deforested lawfully (49,273 ha). More than half of Amazon soy farms have soy-suitable areas that were deforested before 2008 and used for soy in 2019 (1.7 Mha). Taken together, these findings suggest that the opportunity costs of the ASM on current soy farms are low relative to the market access benefits.